Factors influencing COVID-19 vaccination intention among university students : A cross-sectional study in Malaysia - Wong, Chee Yin; Tham, Jen Sern; Foo, Chai Nien; Ng, Foong Leng; Saleha, Shahar; Mohd Nizam, Zahary; Mohd Nazri, Ismail; Tan, Cheng Siang; Hoh, Boon Peng; Subbiah, Vijay Kumar; Lim, Yang Mooi (Elsevier B.V., 2023)
Vaccination is crucial in controlling the spread of the coronavirus disease 2019 (COVID‐19) that triggered the pandemic, but herd immunity can only work with high vaccination coverage in the population. This study aims to measure the COVID‐19 knowledge level and determine the factors influencing COVID‐19 vaccination intention among university students in Malaysia. A cross‐sectional online survey was carried out with 1,274 Malaysian university students in July 2021. Univariate and multivariate analyses were employed to examine the relationships between the study variables. Results showed that the majority of university students had an acceptable level of knowledge of COVID‐19. The knowledge, risk perception of COVID‐19, social norms, and perceived benefit of COVID‐19 vaccination were positively associated with vaccination intention. However, perceived trust in information sources of COVID‐19 vaccination and the government's response to COVID‐19 did not affect the university students’ desire to receive the vaccination. These findings are essential for health policymakers and healthcare providers to implement evidence‐based interventions to increase COVID‐19 vaccination uptake among university students